Jatuh bangun pergerakan Islam di Indonesia - Anwar, Rosihan, 1922-2011.; Fadli Zon Library (Jakarta). (Jakarta : Fadli Zon Library, 2011)
Essays on Islam movement and nationality in Indonesia.
Previously published: Kartika Tama, 1971.